Evidence of linkage to chromosome 9q22.33 in colorectal cancer kindreds from the United Kingdom. - Kemp, Z; Carvajal-Carmona, L; Barclay, E; Gorman, M; Martin, L; Wood, W; Rowan, A; Donohue, C; Spain, S; Jaeger, E; Evans, D; Maher, E; et al. (2006)
About 30% of all colorectal cancers are thought to have a genetic basis and the known predisposing genes can only account for a small fraction of cases. A previous report suggested that a colorectal cancer candidate gene, explaining at least 20% of colorectal cancer cases with family history, was located within a 25 cM region on chromosome 9q22.2-q31.3. We typed 16 polymorphic markers encompassing the region of putative linkage in 57 colorectal tumor families from the United Kingdom. Known Mendelian syndromes had been excluded. We found suggestive evidence of linkage, as positive parametric (HLOD = 1.23) and nonparametric (NPL = 1.21, P = 0.11) LOD scores were obtained by analysis of the whole family set. Enrichment for cases with a priori genetic etiology by analyzing families with at least one person affected at <45 years of age (n = 39 families) gave a maximum multipoint NPL score of 2.65 (P = 0.007). In this group, significant NPL scores >1.67 (P < 0.05) were found in a 6.5 cM region between D9S1851 and D9S277. With a more stringent threshold (NPL>2.4, P < 0.01), the linked region was 1.7 cM between D9S971 and D9S272/D9S173. Exclusion from the analysis of kindreds with a phenotype of multiple polyposis also found evidence of linkage in the same region (NPL = 2.47 at close to D9S277, P = 0.009). The type I transforming growth factor-beta receptor, a prime candidate gene, was excluded as a cause of disease. The results presented here further support the existence of a colorectal cancer susceptibility gene on chromosome 9q and refine its likely location.